Why should we be concerned by internalised racism in global health? - Ferdinand C Mukumbang; Shiva R Mishra; Bipin Adhikari; Chanaki Amaratunga (BMJ Global Health)
Internalised racism constitutes an adoption of beliefs about one’s inferiority, weaknesses or shortcomings as a function of racial hierarchy affecting one’s identity and self-worth, thoughts, emotions and behaviours. Internalised racism stems from widely known and discussed institutional racial discrimination, which perpetuates epistemic injustice, social injustice and health inequities in global health. In this article, reflecting on our experiential knowledge from working on global health, we engage with relevant literature to (1) highlight the concepts associated with internalised racism, (2) explore the potential impacts of internalised racism on individuals, organisations and global health and (3) propose strategies to redress and mitigate its impact on global health practice.